Analysis of the Relationship Between Corporate Governance and Firm Value in Islamic Banks in Indonesia - Devi Devi; Antong Antong; Halim Usman (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This study aims to determine how the relationship between the independent variables, namely corporate governance proxied by managerial ownership, ownership, independent board of commissioners, audit committee, and board of directors based on ASET, BOPO, CAR, and DPK. This study uses a sample of Indonesian Islamic Banks, ASET, BOPO, CAR, and DPK used, namely the last 4 years (2018-2021) in Indonesia, while the data used is secondary data taken from the official government website of the central statistics agency (BPS), annual financial reports collected from BSI (Bank Syariah Indonesia), processed using the reviews application. The data carried out several data analysis tests including a correlation test and a granger causality test. The results of this study are in the correlation coefficient table, ASET has a very weak correlation with CAR and DPK, while BOPO has a perfect negative correlation with AET, CAR, and DPK, CAR has a moderate correlation with DPK, and DPK has a very weak correlation with ASET. Meanwhile, in the granger causality test table BOPO has no significant effect on ASET in Islamic banks in Indonesia, and vice versa, ASET has no significant effect on BOPO. CAR has no significant effect on assets and vice versa, assets have no significant effect on CAR. DPK has no significant effect on assets, and vice versa, assets have no significant effect on DPK. DPK has no significant effect on BOPO and vice versa BOPO has no significant effect on DPK.